Evolution of metallic cardiovascular stent materials: A comparative study among stainless steel, magnesium and zinc. (February 2020) - Fu, Jiayin; Su, Yingchao; Qin, Yi-Xian; Zheng, Yufeng; Wang, Yadong; Zhu, Donghui
Abstract: A cardiovascular stent is a small mesh tube that expands a narrowed or blocked coronary artery. Unfortunately, current stents, regardless metallic or polymeric, still largely fall short to the ideal clinical needs due to late restenosis, thrombosis and other clinical complications. Nonetheless, metallic stents are preferred clinically thanks to their superior mechanical property and radiopacity to their polymeric counterparts. The emergence of bioresorbable metals opens a window for better stent materials as they may have the potential to reduce or eliminate late restenosis and thrombosis. In fact, some bioresorbable magnesium (Mg)-based stents have obtained regulatory approval or under trials with mixed clinical outcomes. Some major issues with Mg include the too rapid degradation rate and late restenosis. To mitigate these problems, bioresorbable zinc (Zn)-based stent materials are being developed lately with the more suitable degradation rate and better biocompatibility. The past decades have witnessed the unprecedented evolution of metallic stent materials from first generation represented by stainless steel (SS), to second generation represented by Mg, and to third generation represented by Zn. To further elucidate their pros and cons as metallic stent materials, we systematically evaluated their performances in vitro and in vivo through direct side-by-side comparisons. Our results demonstrated that tailored Zn-based material with proper configurations could be a promising candidate for a better stent material in the future. Graphical abstract: Image 1